Evidence of cyclic climatic changes recorded in clay mineral assemblages from a continental Paleocene-Eocene sequence, northwestern Argentina - Do Campo, Margarita Diana (2018)
The continental Paleocene-Eocene sequence investigated in this study belongs to the Salta Group, deposited in an intracontinental rift, the Salta Basin (NW Argentina), that evolved from the lower Cretaceous to the middle Paleogene, and is subdivided into the Pirgua, the Balbuena and the Santa Barbara Subgroups. The Maíz Gordo Formation (200 m thick) is the middle unit of the Santa Bárbara Subgroup, deposited during late post-rift sedimentation. We studied the mineralogy of fine-grained horizons of this formation by X-ray diffraction and Scanning Electron Microscopy (SEM) in order to examine the connection between vertical changes in clay mineralogy in alluvial sediments and paleosols, and global paleoclimatic changes registered during the Paleogene. Paleosols vary from calcic vertisols in the lowermost levels, to inseptisols and gleysols in intermediate positions, to gleyed oxisols in the upper section, indicating increased chemical weathering through time. Clay mineral relative abundances vary with a general increase in kaolinite content from bottom to top. However, at one site there are significant variations in kaolinite/muscovite (Kln/Ms) that define five cycles of kaolinite abundance and Kln/Ms. that indicate cyclic patterns of paleoprecipitation and paleotemperature. These are interpreted as several short-lived hyperthermals during the Paleocene-early Eocene in the Southern Hemisphere, which correlate with well-established episodes of warmth documented from the Northern Hemisphere.